In-situ Absorbance Monitoring of NAD+ Reduction Using Platinum-Modified Carbon Paper Electrodes. (December 2020) - Wolfe, Kody D.; Cliffel, David E.; Kane Jennings, G.
Abstract : 2020 H. H. Uhlig Summer Research Fellowship – Summary Report